TOPIC MODELING OF PUBLIC DISCOURSE ON TWITTER ABOUT THE ASSET CONFISCATION BILL USING LATENT DIRICHLET ALLOCATION (LDA) - Azka Bima Aditya; Ahmad Abdul Chamid; Rizkysari Mei Maharani (Kresnamedia Publisher, 2026)
This study examines the structure of public discourse on Twitter regarding the Indonesian Asset Confiscation Bill, a policy initiative aimed at strengthening anti corruption enforcement and ensuring legal certainty. Moving beyond conventional sentiment classification, this research identifies how substantive public concerns are thematically organized within digital debate. A total of 14,319 cleaned and deduplicated tweets collected between January and September 2025 were analyzed using Latent Dirichlet Allocation with the optimal model configuration of nine topics selected based on coherence evaluation to ensure semantic interpretability. The findings reveal nine dominant thematic clusters, with law enforcement and regulatory enactment emerging as the primary focus, followed by legislative process dynamics, protest mobilization, party politics, and institutional accountability. These results indicate that online discourse is structured around normative concerns, particularly procedural clarity, fairness, and institutional legitimacy, rather than driven solely by emotional polarity. Scientifically, this study contributes by shifting the analytical emphasis from sentiment polarity toward systematic thematic mapping of digital political discourse using an optimized LDA framework tailored to Indonesian Twitter data characteristics. Practically, the findings provide policymakers with an evidence based monitoring instrument to identify priority public concerns, strengthen legislative communication strategies, and reduce interpretive ambiguity in sensitive regulatory deliberations.